2010
DOI: 10.1111/j.1749-771x.2010.01100.x
|View full text |Cite
|
Sign up to set email alerts
|

Lower urinary tract symptoms in women and quality of life

Abstract: Lower urinary tract symptoms (LUTSs) are the most common symptoms in women at all age groups worldwide, and their prevalence is increasing with age. LUTSs have a multifactorial status. The risk factors are age, race, pregnancy, birth, menopause, hysterectomy, obesity, chronic cough, depression, profession and family history. LUTSs have negative effects on women's quality of life, especially on the medical, physical, social, psychological, economical and sexual aspects. Studies report a relationship between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 61 publications
2
18
0
1
Order By: Relevance
“…The result was consistent with [20] his study showed that a considerable number of the respondents about two thirds reported poor QoL. Moreever, this goes in the same line by [38] who stated that the quality of life of women with UI is significantly lower than the quality of life of the women without UI. Also, result is consistent with [39] who stated that urinary incontinence have negative effects on women's quality of life, especially on the medical, physical, social, psychological, economical and sexual aspects.…”
Section: From View Point Of Researcher Theses Differences In Results supporting
confidence: 85%
“…The result was consistent with [20] his study showed that a considerable number of the respondents about two thirds reported poor QoL. Moreever, this goes in the same line by [38] who stated that the quality of life of women with UI is significantly lower than the quality of life of the women without UI. Also, result is consistent with [39] who stated that urinary incontinence have negative effects on women's quality of life, especially on the medical, physical, social, psychological, economical and sexual aspects.…”
Section: From View Point Of Researcher Theses Differences In Results supporting
confidence: 85%
“…In addition, LUTS also include symptoms related to pelvic organ prolapse and sexual intercourse, genital and lower urinary tract pain, genito-urinary pain, and syndromes related to lower urinary tract dysfunction 1 . LUTS affects the quality of life of women negatively and is a common health problem 3 . Although the data collection tools, study population, and location vary, the prevalence of at least one LUTS in women has been reported to range between 18.7% and 84.0% in various studies [4][5][6][7][8][9][10][11][12][13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…Although the data collection tools, study population, and location vary, the prevalence of at least one LUTS in women has been reported to range between 18.7% and 84.0% in various studies [4][5][6][7][8][9][10][11][12][13][14][15][16][17] . The LUTS prevalence increases with increasing age in the female 3,4,18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of the symptoms mentioned above can negatively affect the women's quality of life, therefore, LUTS is considered a serious and relevant health problem for women, and its evaluation is important for further treatment (4,5).…”
Section: Introductionmentioning
confidence: 99%